Application of Interventions Progressive Muscle Relaxation to Lower Pain Post OP Appendectomy in RSUD Tenriawaru - Mardiana, Mardiana (Journal for Research in Public Health, 2021)
Appendicitis can occur at any age, but the incidence of appendicitis increases in adolescence and adulthood. Age 20-30 years, which at that age do a lot of activities. This causes the person to ignore dietary nutrition, resulting in difficulty defecating and causing increased pressure in the intestinal cavity and eventually causing blockage of the appendix. The purpose of this study was to apply nursing care to clients post op appendectomy with acute pain problems: therapy Progressive Muscle Relaxation. This study used a case study design with data collection techniques through interviews, physical examination and documentation study. The results of this case study indicate that in the assessment it was found that there were differences in the assessment data obtained for the five clients, the nursing diagnosis that was enforced was acute pain. The intervention arranged is therapy Progressive Muscle Relaxation, the implementation was carried out for three days on the five clients. The conclusion from the results of this study is theresults of the evaluation for 3 days of implementation that nursing care to the five clients who experienced it post op appendectomy with acute pain problems. Progressive Muscle Relaxation can reduce pain from a moderate scale (3) to a scale of none (5) according to outcome which will achieved by the author